Muhammadiyah dan Sekolah : Madrasah Tsanawiyah Muhammadiyah Paraman Ampalu Kabupaten Pasaman Barat 1942-2018 - Fitria Sari; Zul Asri (Jurusan Sejarah FIS UNP, 2022)
This research is a historical study that discuss about Muhammadiyah and school: Muhammadiyah (MTsM) Paraman Ampalu, Pasaman Barat Regency 1942-2018. The purpose of this research is to describe the history of establishment and development of Madrasah Tsanawiyah Muhammadiyah Paraman Ampalu Pasaman Barat Regency 1942-2018. This research uses the historical method with heuristic steps or data collection, after the data is obtained, it is followed by interpretation. Next is source criticism is to verivy or critique data that the author can both from primary sources and secondary source. The final stage is writing history or historiography so that this research can be completed. The result of this study indicate that Madrasah Tsanawiyah Muhammadiyah Paraman Ampalu underwent several stages of development progress and setbacks. Madrasah Tsanawiyah Paraman Ampalu has experienced progress, namely in 1970-1900, where a large number of students enrolled study in the Marasah. Then, no less important, there is a very high level of public awarness to take an anctive role in advancing Madrasah Tsanawiyah Muhammadiyah ParamaN Ampalu.